The Epistemology of Evolutionary Psychology Offers a Rapprochement to Cultural Psychology - Saad, Gad (Frontiers in Psychology, 2020)
Many detractors of evolutionary psychology (EP) presume that adaptive arguments are nothing more than whimsical and unfalsifiable just-so stories. The reality though is that the epistemology of EP is precisely the opposite of this antiquated canard in that it fixes the evidentiary threshold much higher than is typically achieved by most scientists. EP amasses evidence across cultures, time periods, disciplines, paradigms, methodologies, and units of analyses in validating a given scientific explanation. These nomological networks of cumulative evidence stimulate greater interdisciplinarity, lesser methodological myopia, and increased consilience (unity of knowledge). A component in building such nomological networks is to examine phenomena that are cross-culturally invariant (human universals) versus those that vary cross-culturally as adaptive responses (the domain of behavioral ecologists and gene-culture coevolution modelers). The epistemological efficacy of this unique approach is highlighted using two case studies, the sex-specificity of toy preferences and men’s preference for the hourglass figure.